IL-4/IL-13 Axis in Allergic Rhinitis: Elevated Serum Cytokines Levels and Inverse Association With Tight Junction Molecules Expression - Nur Husna, Siti Muhamad; Md Shukri, Norasnieda; Tuan Sharif, Sharifah Emilia; Tan, Hern Tze Tina; Mohd Ashari, Noor Suryani; Wong, Kah Keng (Frontiers in Molecular Biosciences, 2022)
The IL-4/IL-13 axis is involved in the pathogenesis of allergic rhinitis (AR). In this study, we investigated the serum cytokines levels of IL-4, IL-5, IL-6 and IL-13 in AR patients, and the transcript expression levels of their receptors (i.e. IL4R, IL5RA, IL6R and IL13RA1) in nasal epithelial cells of AR patients versus non-allergic controls. Nasal epithelial cells and blood samples of non-allergic controls (n=30) and AR patients (n=30) were collected to examine mRNA expression and serum cytokines levels, respectively. Bioinformatics analyses of IL-4/IL-13 receptor heterodimer association with tight junction (TJ) and JAK/STAT signaling genes were conducted in a gene expression profiling (GEP) dataset (GSE44037) of AR patients (n=12) and healthy controls (n=6). Serum IL-4, IL-5, IL-6 or IL-13 levels, and IL13RA1 transcript expression were significantly higher in AR patients compared with non-allergic controls. IL-4 and IL-13 serum levels were positively correlated with IL13RA1 expression in AR patients but not in non-allergic controls. In the GEP dataset (GSE44037), six TJ (CLDN4, CLDN7, CLDN12, CLDN15, TJP1, TJP2) genes’ expressions were negatively correlated, respectively, with IL-4Rα/IL-13Rα1 heterodimeric receptor expression in AR patients and not in control samples. These six TJ genes contributed to the significant enrichment of tight junction Gene Ontology (GO ID: 0070160). Lastly, STATs DNA binding motif analysis showed that each of these TJ genes contains STATs binding consensus sequence within intronic and intergenic regions. Our results suggest that increased IL-4/IL-13 serum cytokines levels may contribute to decreased TJs expression via IL-4Rα/IL-13Rα1 heterodimeric receptor in nasal epithelium of AR patients.